TECHNIQUE FOR SUSTAINABLE DEVELOPMENT ALONG TRISULA WATERFALL (COBAN TRISULA) - RANU PANI, BROMO TENGGER SEMERU NATIONAL PARK: A CASE OF EPIPHYTIC ORCHID CONSERVATION - Afifah Nur Aulia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2019)
The purpose of this study is to develop a technique for sustainable development of epiphytic orchid conservation, identify the types of epiphytic orchid host trees and identify the types of epiphytic orchids along the Trisula waterfall (Coban Trisula) to Ranu Pani. This research was conducted in October 2018 - April 2019 in Trisula waterfall (Coban Trisula) to Ranu Pani. A floristic survey with 9.3-miles exploration in Trisula waterfall (Coban Trisula) to Ranu Pani. Observation of host trees was carried out by observing individual morphological characteristics and referring to the Orchids of Java literature. It is important for the reforestation of potential trees that can be used as hosts by epiphytic orchids and the limitation of the function shifting of land as settlements, agriculture, plantations so, the forest area is wider and the epiphytic orchids are increasingly preserved. Identification of host trees and identification of epiphytic orchids need to support sustainable development as an effort to conserve epiphytic orchids. The types of host trees, they are: Kukrup (Engelhardtia spicata), Cemara gunung (Casuarina junghuhniana), Anggrung (Trema orientalis), Dadap putih (Acer laurinum), Trete (Celtis sp.), Bangkongan (Turpinia spaenocarpa), Suren (Toona sureni), Pamoung (Macropanax dispermus), Pasang (Lithocarpus sundaicus), Tutup (Mallotus paniculatus), Genitri (Elaeocarpus ganitri) and Astronia spectabilis. The types of epiphytic orchids found are Eria moluccana, Schoenorchis juncifolia, Vanda limbate, Agrostophyllum sp., Appendicula sp., Bulbophyllum macrantum, Bulbophyllum miniatum, Bulbophyllum obtusipetalum, Bulbophyllum sp. I, Coelogyne miniata, Dendrobium linearifolium, Dendrobium hasseltii, Dendrobium sanguinolentum, Dendrochilum sp., Eria bogoriensis, Eria hyacinthoides, Eria longifolia, Flickingeria aureiloba, Liparis parviflora, Thrixspermum subulatum, Tuberolabium odoratisimum, Vanda tricolor